IMPACT OF PANDEMIC COVID-19 AND ECONOMIC ACTIVITY ON AIR QUALITY IMPROVEMENT - Mohammad Rofiuddin; Rosana Eri Puspita; Saiful Anwar; Arna Asna Annisa; Rifda Nabila; Desy Nur Pratiwi (Universitas Tidar, 2021)
Pandemic covid-19 presents a policy of tightening the mobility of the population, which directly impacts the reduced mobility of transportation, private transportation, and public transportation. Economic activity also under pressure from the existence of pandemic covid-19, in which economic activity is a source of air pollution for a large part of the country. The purpose of the study to find out the impact of pandemic covid-19 and economic growth on air quality during the pandemic is in 2020. The research method uses a multiple regression approach with a sample count of 80 countries. The results showed that economic growth has no impact on improving air quality and does not prove the environmental Kuznets curve between development and air pollution. In contrast, the increase in cases of covid-19 has the effect of lowering air pollution in each country. This condition occurs because covid restricts the population to activities, which also affects the activities of the company to produce.